Hadith #2628 - Sahih al-Bukhari - Talha bin 'Abdul Malik طلحة بن عبد الملك الأيلي (Sahih al-Bukhari)
I asked `Abdullah bin Abu `Aufa “Did the Prophet (ﷺ) make a will?” He replied, “No,” I asked him, “How is it then that the making of a will has been enjoined on people, (or that they are ordered to make a will)?” He replied, “The Prophet (ﷺ) bequeathed Allah’s Book (i.e. Qur’an).
Grade: Sahih

Hadith #4260 - Sahih al-Bukhari - Talha bin 'Abdul Malik طلحة بن عبد الملك الأيلي (Sahih al-Bukhari)
I asked `Abdullah bin Abu `Aufa “Did the Prophet (ﷺ) make a will? ‘ He replied, “No.” I further asked, “How comes it that the making of a will was enjoined on the people or that they were ordered to make it? ” He said, “The Prophet (ﷺ) made a will concerning Allah’s Book.”
Grade: Sahih

Hadith #4815 - Sahih al-Bukhari - Talha bin 'Abdul Malik طلحة بن عبد الملك الأيلي (Sahih al-Bukhari)
I asked `Abdullah bin Abi `Aufa, “Did the Prophet (ﷺ) make a will (to appoint his successor or bequeath wealth)?” He replied, “No.” I said, “How is it prescribed then for the people to make wills, and they are ordered to do so while the Prophet (ﷺ) did not make any will?” He said, “He made a will wherein he recommended Allah’s Book.”
Grade: Sahih